Microplastics in Aquatic Ecosystems: Detection, Impact, and Bioremediation Strategies - Kaushik, Dr. Naresh; Sohal , Jagmeet; Dash, Dr. Aditya Kishore; Sathish , Dr. S.; Chaudhary , Anisha; Manjunath , ‎Honganur Raju; Nanda, Simranjeet (International Journal of Basic and Applied Sciences, 2025)
Plastic items are practical, cost-effective, portable, and resilient; thus, they are extensively used daily. Microplastics (MP) durability against degradation results in plastic trash persisting in the surroundings for several years. Microplastics, particles less than 5 mm in diameter, are developing environmental contaminants that endanger habitats and human well-being. MP-contaminated pollutants are eventually discharged into Aquatic Ecosystems (AE) and directly consumed by creatures within a specific environment. The MP elements also provide a secondary danger to AE by adsorbing adjacent water contaminants. The excessive release of billions of tons of plastic garbage annually from both home and industrial sources results in the accumulation of decomposed MP in diverse AE, leading to contamination and entry into the food supply chain. This research primarily examines the detection and impact of the discharge of MP into the AE and the potential effects of these hazardous micro-sized fragments on human well-being and aquatic organisms. This paper succinctly addresses the removal of MP from wastewater and AE via several bioremediation strategies.